Broad phenotypic spectrum in familial adenomatous polyposis; from early onset and severe phenotypes to late onset of attenuated polyposis with the first manifestation at age 72 - Johannsson Oskar; Ericsson Mats; Kristoffersson Ulf; Nilbert Mef; Rambech Eva; Mangell Peter (BMC, 2008)
Abstract Background Familial adenomatous polyposis (FAP) is typically characterized by multiple colonic polyps and frequent extracolonic features. Whereas the number of colonic polyps has been linked to the APC gene mutation, possible genotype-phenotype correlations largely remain to be defined for the extracolonic manifestations. Methods Full genomic sequencing combined with multiplex ligation-dependent probe amplification was used to identify APC gene mutations, which were correlated to the clinical presentations. Results 10 novel APC gene mutations were identified in 11 families. A broad spectrum of extracolonic manifestations was identified in most of these individuals. Two sisters with an insertion in codon 528 (c.1582_1583insGC) both showed severe phenotypes with classical polyposis, upper gastrointestinal polyps and thyroid cancer. A woman with a 3'APC mutation (c.5030_5031insAA) developed colon cancer at age 72 as the first manifestation of attenuated FAP. Conclusion With an increasing number of FAP families diagnosed, a broad and variable tumor spectrum and a high frequency of extracolonic manifestations are gradually recognized. We report novel APC mutations and present two FAP cases that suggest familial aggregation of thyroid cancer and demonstrate the need to consider attenuated FAP also among elderly patients with colon cancer.